The Effect of Isometric Exercise on Pain, Muscle Strength and Risk of Infection in Patients with Closed Orif (L) Femur Shaft Fracture Lower Extremity - Nur Asnah Sitohang; Boiolifu Lafau (GLOBAL HEALTH SCIENCE GROUP, 2025)
Femoral shaft fracture is a serious injury commonly caused by high-energy trauma and often requires Open Reduction Internal Fixation (ORIF). Patients following ORIF are at risk of acute pain, impaired physical mobility, and infection due to surgical wounds and implant placement. Femoral shaft fracture is a serious injury commonly caused by high-energy trauma and often requires Open Reduction Internal Fixation (ORIF). Patients following ORIF are at risk of acute pain, impaired physical mobility, and infection due to surgical wounds and implant placement. This study employed a single-case design with a nursing care approach. The subject was a 24-year-old male patient who sustained a closed left femoral shaft fracture due to a traffic accident and underwent ORIF. Nursing interventions included isometric exercises based on the protocol developed by Khosrojerdi et al., performed four times daily for five consecutive days. Pain intensity, muscle strength, and signs of infection were evaluated throughout the intervention period. The evaluation showed a reduction in pain intensity from a Numerical Pain Rating Scale (NPRS) score of 7 to 3. Lower extremity muscle strength improved to grade 4/5 on the Manual Muscle Testing (MMT) scale. No signs of infection were observed during the intervention period. Isometric exercise was effective in reducing pain and improving muscle strength and mobility in a patient with a femoral shaft fracture following ORIF, supporting its use as a nursing intervention in postoperative orthopaedic care.